Efektivitas Pelatihan Manajemen Karir untuk Meningkatkan Kemandirian Memilih Karir pada Siswa SMK - Murni, Candra; Matulessy, Andik; Pratitis, Niken Titi (Faculty of Psychology, Universitas 17 Agustus 1945 Surabaya, 2019)
This research aims to determine the effectiveness of career management training to provide self-reliance on the students who prefer SMK. This research is a quantitative study with experimental methods that use two group pre test-post test design. The subject of a trial scale of 58 students from a population of 455 students and 40 students who have low self-reliance are selected as samples of research. The measuring instrument of this study in the form of a self-reliance choose career based on Steinberg's proven self-reliance aspect has proved valid and reliable. Analyzing the data using the test analysis technique T. Results of the study proved that effective career management training increased independence of choosing a VOCATIONAL student career, so the research hypothesis was accepted (P < 0.01)